2022
DOI: 10.1002/cpt.2539
|View full text |Cite
|
Sign up to set email alerts
|

OX40L Inhibition Suppresses KLH‐driven Immune Responses in Healthy Volunteers: A Randomized Controlled Trial Demonstrating Proof‐of‐Pharmacology for KY1005

Abstract: The safety, tolerability, immunogenicity, and pharmacokinetic (PK) profile of an anti‐OX40L monoclonal antibody (KY1005, currently amlitelimab) were evaluated. Pharmacodynamic (PD) effects were explored using keyhole limpet hemocyanin (KLH) and tetanus toxoid (TT) immunizations. Sixty‐four healthy male subjects (26.5 ± 6.0 years) were randomized to single doses of 0.006, 0.018, or 0.05 mg/kg, or multiple doses of 0.15, 0.45, 1.35, 4, or 12 mg/kg KY1005, or placebo (6:2). Serum KY1005 concentrations were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…Because of the lower immunogenicity, subunit KLH is often used concurrently with an adjuvant, such as aluminum hydroxide (Edelman, 1980). Out of the 9 studies that used an adjuvant together with subunit KLH, participants were immunized with subunit KLH adsorbed to aluminum hydroxide in 7 studies (Boulton et al, 2012;Poirier et al, 2016;Saghari et al, 2020;Saghari et al, 2022;Smith et al, 2004a;Smith et al, 2004b;Spazierer et al, 2009). Valdez H, et al, 2000(Valdez et al, 2000 TIA*** Proliferation 10x (5-20x)** Kantele A, et al, 1999(Kantele et al, 1999 IgM increased (variability unclear) de Fijter JW, et al, 1996(Fijter et al, 1996 Snyder BK, et al, 1993(Snyder et al, 1993 TIA*** Proliferation 3.8x (-1.7-9.5x) Falconer AE, et al, 1992(Falconer et al, 1992 Immunizations with doses of 1 μg-5,000 μg have been reported, with 100 μg being the most frequently used dose (Figure 2).…”
Section: Klh Immunization and Rechallengementioning
confidence: 99%
See 4 more Smart Citations
“…Because of the lower immunogenicity, subunit KLH is often used concurrently with an adjuvant, such as aluminum hydroxide (Edelman, 1980). Out of the 9 studies that used an adjuvant together with subunit KLH, participants were immunized with subunit KLH adsorbed to aluminum hydroxide in 7 studies (Boulton et al, 2012;Poirier et al, 2016;Saghari et al, 2020;Saghari et al, 2022;Smith et al, 2004a;Smith et al, 2004b;Spazierer et al, 2009). Valdez H, et al, 2000(Valdez et al, 2000 TIA*** Proliferation 10x (5-20x)** Kantele A, et al, 1999(Kantele et al, 1999 IgM increased (variability unclear) de Fijter JW, et al, 1996(Fijter et al, 1996 Snyder BK, et al, 1993(Snyder et al, 1993 TIA*** Proliferation 3.8x (-1.7-9.5x) Falconer AE, et al, 1992(Falconer et al, 1992 Immunizations with doses of 1 μg-5,000 μg have been reported, with 100 μg being the most frequently used dose (Figure 2).…”
Section: Klh Immunization and Rechallengementioning
confidence: 99%
“…Valdez H, et al, 2000(Valdez et al, 2000 TIA*** Proliferation 10x (5-20x)** Kantele A, et al, 1999(Kantele et al, 1999 IgM increased (variability unclear) de Fijter JW, et al, 1996(Fijter et al, 1996 Snyder BK, et al, 1993(Snyder et al, 1993 TIA*** Proliferation 3.8x (-1.7-9.5x) Falconer AE, et al, 1992(Falconer et al, 1992 Immunizations with doses of 1 μg-5,000 μg have been reported, with 100 μg being the most frequently used dose (Figure 2). (Birdsall and Rossen, 1983;Boulton et al, 2012;Husby et al, 1994;Kantele et al, 1999;Kantele et al, 2011;Kraus et al, 2004;Lange et al, 2003;Moldoveanu et al, 2004;Ochs et al, 1988;Otterhaug et al, 2021;Paty et al, 1975;Smith et al, 2004a;Smith et al, 2004b;Spazierer et al, 2009;Poirier et al, 2016;Saghari et al, 2020;Saghari et al, 2022;Snyder et al, 1993;Waldo et al, 1994) Higher KLH immunization doses have been used in earlier studies and in studies using subunit KLH alone compared to studies using HMW-KLH or subunit KLH with an adjuvant (Table 1). Notably, Belson et al used a high KLH immunization dose of 5,000 μg causing a participant withdrawal rate of approximately 38% due to large local reactions following a single subcutaneous administration (Belson et al, 2016).…”
Section: Klh Immunization and Rechallengementioning
confidence: 99%
See 3 more Smart Citations